Aqueous polyurethane and use thereof for the preparation of double-sidedly dissimilar adhesive patches

CN117843908BActive Publication Date: 2026-10-27SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311845689.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2026-10-27
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

例如,公布号为CN103420868A的发明专利,公开了含双季铵盐二胺或二醇单体制备的聚氨酯乳液,具有很好的生物相容性、抗粘附、抗生物膜形成和杀菌性能;然而,其虽然表现出优异的抗菌性能,但却未能成膜形成具有Janus特性的生物膜材;另有采用多肽二胺作为扩链剂制备得到外层亲水内层疏水的双层结构水性聚氨酯材料的报道(CN108840991A),该材料虽表现出内外层性能相异的特性,但仅具有抗菌和双面防污的用途,并未表现出生物粘附性

Benefits of technology

[0041]本发明有益效果:本发明提供了一种新型水性聚氨酯材料,通过特定的原料种类和用量,在特定的成膜条件下,制备得到的聚氨酯膜表现出独特的一面粘连,另一面防粘连的非对称性,作为非对称粘附的Janus生物粘附贴片,粘合面能够有效实现生物组织粘附闭合创口,防粘面则能有效避免正常组织粘连;同时,季铵盐的引入使贴片具有良好的抗菌性能,可促进皮肤伤口闭合和感染伤口愈合。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117843908B_ABST
    Figure CN117843908B_ABST
Patent Text Reader

Abstract

The application provides a kind of water-based polyurethane and its preparation two-way adhesive patch, belong to the field of biomedical materials.The water-based polyurethane of the application is prepared from the following molar fractions of raw materials: soft segment component 8-12 parts, diisocyanate 20-25 parts, chain extender 8-12 parts;The application also provides an emulsion of the above water-based polyurethane, and a polyurethane film obtained by film formation of the emulsion in a specific manner.The polyurethane film exhibits unique one-side adhesion and the other side anti-adhesion asymmetry, the adhesive surface can effectively realize biological tissue adhesion to close the wound, the anti-adhesion surface can effectively avoid normal tissue adhesion, while showing good biocompatibility and antibacterial performance, can promote skin wound closure and infected wound healing, as an asymmetric adhesion Janus biological adhesive patch, has broad application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention provides a waterborne polyurethane and its use in preparing biaxially shaped adhesive patches, belonging to the field of biomedical materials. Background Technology

[0002] Closure of damaged tissue is a crucial step in reconstructing its structure and function. Currently, surgical sutures are primarily used to close wounds and surgical incisions. However, suturing can damage fragile tissues, increasing the risk of bacterial infection, and is time-consuming and technically demanding. Medical tissue adhesives hold promise as an adjunct or alternative to traditional surgical sutures. However, existing tissue adhesives often fail to achieve the desired results. Furthermore, most tissue adhesives are indiscriminate double-sided adhesives, easily adhering to normal tissue on the back, posing postoperative risks. Additionally, double-sided adhesives readily adhere to various substrates in the environment, increasing the risk of wound microbial infection and causing inconvenience. These limitations hinder the application of traditional double-sided bio-adhesives in tissue repair and clinical practice.

[0003] Several strategies, such as unilateral ion blocking, immersion methods, and stepwise synthesis, have been reported to prepare asymmetric surface properties. However, these strategies involve complex manufacturing processes and multiple steps, and interfacial bonding issues exist between composite layers. This can lead to poor repeatability and controllability of patch properties, significantly limiting their practical application and large-scale production. Therefore, developing high-performance asymmetric Janus bioadhesive patches remains a challenge. Adhesives typically adhere to substrates through interfacial interactions such as hydrogen bonds, covalent bonds, electrostatic interactions, and van der Waals forces. Therefore, there is an urgent need for simple methods to tune the ability of adhesives to interact with the substrate on both sides to prepare asymmetric adhesive patches.

[0004] Waterborne polyurethane is a multi-block polymer that has been applied in the biomedical field due to its good biocompatibility and flexible structural design, making it a potential choice for preparing bioadhesive patches. Quaternary ammonium salts, as cationic surfactants, have excellent antibacterial effects. Currently, there are reports of introducing quaternary ammonium salt diols or diamines as chain extenders into waterborne polyurethane systems. For example, invention patent CN103420868A discloses a polyurethane emulsion prepared with bisquaternary ammonium salt diamine or diol monomers, which has good biocompatibility, anti-adhesion, anti-biofilm formation, and bactericidal properties; however, although it exhibits excellent antibacterial properties, it has failed to form a biofilm material with Janus properties; another report (CN108840991A) describes the preparation of a bilayer waterborne polyurethane material with a hydrophilic outer layer and a hydrophobic inner layer using polypeptide diamine as a chain extender. Although this material exhibits different properties between the inner and outer layers, it only has antibacterial and double-sided antifouling applications and does not show bioadhesion. Therefore, the preparation of polyurethane materials with bi-sided adhesive bioadhesive patches still needs further exploration. Summary of the Invention

[0005] This invention provides an aqueous polyurethane, prepared from the following raw materials in the following molar proportions: 5-15 parts of a soft segment component, 11-42 parts of a diisocyanate, and 5-15 parts of a chain extender; wherein the soft segment component is a mixture of a hydrophilic diol or diamine and a hydrophobic diol or diamine, and the molar fraction of the hydrophobic diol or diamine in the soft segment component is 20%-100%; and the chain extender is a quaternary ammonium salt chain extender or a mixture thereof with a non-quaternary ammonium salt chain extender.

[0006] The structure of the quaternary ammonium salt chain extender is shown in Formula I:

[0007]

[0008] Where R is a hydroxyl or amino group, and X is a halogen; p and q are each independently selected from integers from 1 to 5, and n is selected from integers from 2 to 17.

[0009] Furthermore, the above-mentioned waterborne polyurethane is prepared from the following molar amounts of raw materials: 8-12 parts of soft segment component, 20-25 parts of diisocyanate, and 8-12 parts of chain extender; the molar fraction of hydrophobic diol or diamine in the soft segment component is 50%-83%; and the molar fraction of non-quaternary ammonium salt chain extender in the chain extender is 0%-75%.

[0010] Furthermore, the above-mentioned waterborne polyurethane is prepared from the following molar proportions of raw materials: 10 parts of soft segment component, 22 parts of diisocyanate, and 10 parts of chain extender; the molar fraction of hydrophobic diol or diamine in the soft segment component is 83%; and the molar fraction of non-quaternary ammonium salt chain extender in the chain extender is 25%.

[0011] Furthermore, the hydrophilic diol or diamine mentioned above is selected from one or more of PEG and Ymer N-120, preferably PEG;

[0012] The hydrophobic diol or diamine mentioned above is selected from one or more of polyether diols, copolyether diols, polyester diols, copolyester diols, polysiloxane diols and polycarbonate diols, preferably PPG or PTMG;

[0013] The diisocyanate mentioned above is selected from any one or more of lysine-derived diisocyanate, hexamethylene diisocyanate, trimethyl 1,6-hexamethylene diisocyanate, isophorone diisocyanate, cyclohexanedimethylene diisocyanate, 4,4-dicyclohexylmethane diisocyanate or 1,4-cyclohexane diisocyanate, preferably isophorone diisocyanate;

[0014] The aforementioned non-quaternary ammonium salt chain extender is any one or more of ethylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, 1,4-cyclohexanediol, dimethylolpropionic acid, diethylene glycol, tetraethylene glycol, hydrazine, ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,6-hexanediamine, isophoronediamine, ethanolamine, propanolamine, or lysine, preferably lysine;

[0015] R is a hydroxyl group, p is 2 or 3, q ​​is 2 or 3, and n is 5 to 15. Preferably, the quaternary ammonium salt chain extender is...

[0016]

[0017] The present invention also provides an aqueous polyurethane emulsion, which is obtained by emulsifying and dispersing the above-mentioned aqueous polyurethane in water.

[0018] The present invention also provides a method for preparing the above-mentioned aqueous polyurethane emulsion, comprising the following steps:

[0019] (1) The dry and anhydrous soft segment component is added with diisocyanate and catalyst under inert gas protection and reacted at 78-82℃ for 1.5-2.5h;

[0020] (2) Cool to room temperature, add quaternary ammonium salt chain extender, and react at 53-56℃ for 2.5-3.5h;

[0021] (3) Without adding non-quaternary ammonium salt chain extenders, or with adding non-quaternary ammonium salt chain extenders, react at room temperature for 3 to 8 minutes, then stir and emulsify at a speed higher than 1000 rpm for 0.8 to 1.2 hours.

[0022] Preferably, the catalyst in step (1) is organic bismuth, the amount of which is 1‰ of the total amount of raw materials, the reaction temperature is 80℃, and the time is 2h;

[0023] The reaction temperature in step (2) is 55℃, and the reaction time is 3h.

[0024] In step (3), the non-quaternary ammonium salt chain extender is added and the reaction time at room temperature is 5 min, and the stirring and emulsification time is 1 h.

[0025] The present invention also provides a polyurethane membrane, which is prepared by drying the above-mentioned aqueous polyurethane emulsion to remove the solvent; the preparation method includes the steps of pouring the above-mentioned aqueous polyurethane emulsion into a mold and drying at room temperature for more than 48 hours.

[0026] Further, the above-mentioned polyurethane membrane preparation method is as follows: pour the above-mentioned aqueous polyurethane emulsion into a mold, dry at room temperature for 70-75 hours, dry at 45-55°C for 45-50 hours, and then vacuum dry at 45-55°C for 45-50 hours; preferably, dry at room temperature for 72 hours, dry at 50°C for 48 hours, and then vacuum dry at 50°C for 48 hours.

[0027] The present invention also provides a method for preparing a polyurethane film, comprising the steps of pouring an aqueous polyurethane emulsion into a mold and drying it at room temperature for more than 48 hours.

[0028] The aqueous polyurethane emulsion is obtained by emulsifying and dispersing aqueous polyurethane in water; the raw materials for preparing the aqueous polyurethane include a quaternary ammonium salt chain extender; the structure of the quaternary ammonium salt chain extender is shown in Formula I:

[0029]

[0030] Where R is a hydroxyl or amino group, and X is a halogen; p and q are each independently selected from integers from 1 to 5, and n is selected from integers from 2 to 17;

[0031] Preferably, the method includes the following steps:

[0032] (a) Pour the above-mentioned aqueous polyurethane emulsion into a mold and dry at room temperature for 70-75 hours;

[0033] (b) Dry at 45–55℃ for 45–50 hours;

[0034] (c) Vacuum drying at 45-55℃ for 45-50 hours.

[0035] The present invention also provides the use of the above-mentioned waterborne polyurethane, or waterborne polyurethane emulsion, or polyurethane film in the preparation of adhesive patches.

[0036] Explanation of terminology in this invention:

[0037] PEG: polyethylene glycol; PPG: polypropylene glycol; IPDI: isophorone diisocyanate; Lys: lysine; PTMG: polytetrahydrofuran diol.

[0038] Inert gases: nitrogen, helium, neon, argon, krypton, xenon, or radon.

[0039] Room temperature: 20℃~30℃.

[0040] In this invention, "top" refers to the film surface that does not contact the mold during the polyurethane film formation process; "bottom" refers to the surface that contacts the mold, opposite to "top".

[0041] Beneficial effects of the present invention: The present invention provides a novel waterborne polyurethane material. By using specific types and amounts of raw materials and under specific film-forming conditions, the polyurethane film prepared exhibits a unique asymmetric property of one side being adhesive and the other side being anti-adhesive. As an asymmetric adhesive Janus bioadhesive patch, the adhesive side can effectively achieve biological tissue adhesion and wound closure, while the anti-adhesive side can effectively prevent adhesion of normal tissue. At the same time, the introduction of quaternary ammonium salt gives the patch good antibacterial properties, which can promote skin wound closure and healing of infected wounds.

[0042] Obviously, based on the above description of the present invention, and according to common technical knowledge and conventional methods in the field, various other modifications, substitutions or alterations can be made without departing from the basic technical concept of the present invention.

[0043] The following detailed embodiments further illustrate the above-described content of the present invention. However, this should not be construed as limiting the scope of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention. Attached Figure Description

[0044] Figure 1 These are the water contact angle test results of the polyurethane membranes in the embodiments and comparative examples of the present invention.

[0045] Figure 2 These are the infrared test results of the polyurethane films in the embodiments and comparative examples of the present invention.

[0046] Figure 3 These are the N element XPS test results of the polyurethane membranes in the embodiments and comparative examples of this invention.

[0047] Figure 4 This is an adhesion diagram of the top and bottom of the QLPU75 polyurethane film of the present invention to different substrates.

[0048] Figure 5 These are the adhesion strength test results of the top and bottom of the polyurethane film to pigskin in the embodiments and comparative examples of the present invention.

[0049] Figure 6 These are the results of comparative tests on the adhesion strength of the top and bottom of the polyurethane film to pigskin.

[0050] Figure 7 These are the results of live and dead cell staining after co-incubating the QLPU75 polyurethane membrane of this invention with L929 cells for 1 day and 3 days.

[0051] Figure 8 These are the MTT test results of the QLPU75 polyurethane membrane extract of this invention.

[0052] Figure 9 This invention demonstrates the contact sterilization effect of polyurethane membranes on Escherichia coli and Staphylococcus aureus in embodiments and comparative examples of the present invention.

[0053] Figure 10 These are the contact sterilization test results of the polyurethane membranes in the embodiments and comparative examples of the present invention against Escherichia coli and Staphylococcus aureus.

[0054] Figure 11 These are the characterization results of the hemostatic performance of the QLPU75 polyurethane membrane of this invention.

[0055] Figure 12 (a) Demonstration of the effects of commercial dressings and the QLPU75 polyurethane membrane of the present invention on repairing infected wounds, with untreated wounds as a control; (b) Closure rate of wounds repaired by the control group, commercial dressings, and the QLPU75 polyurethane membrane of the present invention on days 3, 7, and 17; (c) Schematic diagram of wound contraction within 17 days of repair by the control group, commercial dressings, and the QLPU75 polyurethane membrane of the present invention; (d) Images of skin tissue after repair by the control group, commercial dressings, and the QLPU75 polyurethane membrane of the present invention 7 and 17 days later (black scale bar: 1000 μm, red scale bar: 200 μm, yellow scale bar: 500 μm).

[0056] Figure 13 Immunofluorescence images of regenerated skin tissue labeled with TNF-α (red), VEGF (green), and DAPI (blue). Detailed Implementation

[0057] As an example, the quaternary ammonium salt chain extender used in the embodiments of the present invention is a dodecanoic dihydroxy quaternary ammonium salt chain extender (Q12), but this is not intended to limit the structure of the quaternary ammonium salt chain extender used in the present invention. The synthesis method of Q12 is as follows:

[0058]

[0059] N-methyldiethanolamine (50 mmol), dodecane bromide (55 mol), and isopropanol (200 mL) were refluxed at 80 °C and stirred for 24 hours. The mixture was cooled to room temperature, and the isopropanol was removed by rotary evaporation to concentrate the crude sample. Acetone was then added and cooled, resulting in white crystals. The crystals were recrystallized at least three times in acetone to obtain a white solid powder, which is Q12.

[0060] Example 1: Synthesis of QLPU100 waterborne polyurethane emulsion

[0061] 8.3 mM of dried and dehydrated PPG2000 (i.e., PPG with a number average molecular weight of 2000) and PEG1450 (i.e., PPG with a number average molecular weight of 1450) were placed in a reactor. Under nitrogen protection, 22 mM IPDI and 1‰ of the total raw material amount of organic bismuth catalyst were added to the reaction flask, and prepolymerization was carried out at 80°C for 2 hours. After cooling to room temperature, 10 mM chain extender Q12 was added to the reaction system, and chain extension reaction was carried out at 55°C for 3 hours. Then, the mixture was stirred and emulsified at 1500 rpm at room temperature for 1 hour to obtain the waterborne polyurethane emulsion QLPU100.

[0062] Example 2: Synthesis of QLPU75 waterborne polyurethane emulsion

[0063] 8.3 mM of dried and dehydrated PPG2000 (i.e., PPG with a number average molecular weight of 2000) and PEG1450 (i.e., PPG with a number average molecular weight of 1450) were placed in a reactor. Under nitrogen protection, 22 mM of IPDI and 1‰ of the total raw material amount of organic bismuth catalyst were added to the reaction flask, and prepolymerization was carried out at 80°C for 2 h. After cooling to room temperature, 7.5 mM of chain extender Q12 was added to the reaction system, and chain extension reaction was carried out at 55°C for 3 h. Then, 2.5 mM of lysine (Lys) was added to the reaction system, and chain extension was carried out at room temperature for 5 min. Finally, emulsification was carried out at room temperature at 1500 rpm for 1 h to obtain the waterborne polyurethane emulsion QLPU75.

[0064] Example 3: Synthesis of QLPU50 waterborne polyurethane emulsion

[0065] The preparation method is the same as in Example 2, except that the amount of chain extender Q12 is 5mM and the amount of lysine is 5mM, to obtain the waterborne polyurethane emulsion QLPU50.

[0066] Example 4: Synthesis of QLPU25 waterborne polyurethane emulsion

[0067] The preparation method is the same as in Example 2, except that the amount of chain extender Q12 is 2.5 mM and the amount of lysine is 7.5 mM, resulting in an aqueous polyurethane emulsion QLPU25.

[0068] Example 5: Synthesis of waterborne polyurethane emulsion obtained from QLPU55-100

[0069] The preparation method is the same as in Example 1, except that the amount of PPG2000 is 5 mM and the amount of PEG1450 is 5 mM, resulting in the waterborne polyurethane emulsion QLPU55-100.

[0070] Example 6: Synthesis of QLPUPTMG-100 waterborne polyurethane emulsion

[0071] The preparation method is the same as in Example 1, except that PPG2000 is replaced with PTMG2000 (i.e., PTMG with a number average molecular weight of 2000) to obtain the waterborne polyurethane emulsion QLPUPTMG-100.

[0072] Comparative Example 1: Synthesis of QLPU0 Waterborne Polyurethane Emulsion

[0073] The preparation method is the same as in Example 2, except that the amount of chain extender Q12 is 0 mM and the amount of lysine is 10 mM.

[0074] The raw material usage amounts for Examples 1-6 and Comparative Example 1 are shown in Table 1.

[0075] Table 1

[0076]

[0077]

[0078] Example 7: Preparation of QLPU100 polyurethane membrane

[0079] The aqueous polyurethane emulsion of Example 1 was poured into a glass dish and evaporated at room temperature for 72 hours. Then it was placed in a 50°C oven and dried for 48 hours. Finally, it was placed in a 50°C vacuum oven and dried for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm.

[0080] Example 8: Preparation of QLPU75 polyurethane film

[0081] The aqueous polyurethane emulsion of Example 2 was poured into a glass dish and evaporated at room temperature for 72 hours. Then it was placed in a 50°C oven and dried for 48 hours. Finally, it was placed in a 50°C vacuum oven and dried for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm.

[0082] Example 9: Preparation of QLPU50 polyurethane film

[0083] The aqueous polyurethane emulsion of Example 3 was poured into a glass dish, evaporated at room temperature for 72 hours, and then placed in a 50°C oven for 48 hours. After that, it was placed in a 50°C vacuum oven for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm.

[0084] Example 10: Preparation of QLPU25 polyurethane film

[0085] The aqueous polyurethane emulsion of Example 4 was poured into a glass dish and evaporated at room temperature for 72 hours. Then it was placed in a 50°C oven and dried for 48 hours. Finally, it was placed in a 50°C vacuum oven and dried for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm.

[0086] Example 11: Preparation of QLPU55-100 polyurethane film

[0087] The aqueous polyurethane emulsion of Example 5 was poured into a glass dish and evaporated at room temperature for 72 hours. Then it was placed in a 50°C oven and dried for 48 hours. Finally, it was placed in a 50°C vacuum oven and dried for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm.

[0088] Example 12: Preparation of QLPUPTMG-100 polyurethane membrane

[0089] The aqueous polyurethane emulsion of Example 6 was poured into a glass dish, evaporated at room temperature for 72 hours, and then placed in a 50°C oven for 48 hours. After that, it was placed in a 50°C vacuum oven for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm.

[0090] Comparative Example 2: Preparation of QLPU0 polyurethane membrane

[0091] The aqueous polyurethane emulsion of Comparative Example 1 was poured into a glass dish and evaporated at room temperature for 72 hours. Then it was placed in a 50°C oven and dried for 48 hours. Finally, it was placed in a 50°C vacuum oven and dried for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm.

[0092] Comparative Example 3: Preparation of QLPU75-50 polyurethane membrane

[0093] The aqueous polyurethane emulsion from Example 2 was poured into a glass dish and dried in a 50°C oven for 72 hours. Then it was dried in a 50°C vacuum oven for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm, named QLPU75-50.

[0094] Comparative Example 4: Preparation of QLPU75-75 polyurethane film

[0095] The aqueous polyurethane emulsion from Example 2 was poured into a glass dish and dried in a 75°C oven for 72 hours. Then it was dried in a 50°C vacuum oven for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm, named QLPU75-75.

[0096] Comparative Example 5: Preparation of QLPU75-100 polyurethane membrane

[0097] The aqueous polyurethane emulsion of Example 2 was poured into a glass dish and dried in a 100°C oven for 72 hours. Then it was dried in a 50°C vacuum oven for another 48 hours to obtain a polyurethane film with a thickness of about 200 μm, named QLPU75-100.

[0098] The performance of the polyurethane films prepared in the embodiments and comparative examples of the present invention was characterized using the following characterization instruments and methods:

[0099] Hydrophilicity / hydrophobicity performance test:

[0100] The water contact angles at the top and bottom of the polyurethane membrane were determined at room temperature using the static drop method. During the measurement, 2 μL of deionized water was dropped onto the surface of the polyurethane membrane, and the water contact angle results were obtained using a water contact angle meter (DSA100, Germany).

[0101] Microstructure characterization:

[0102] Using a Nicolet iS 50 infrared spectrometer, the infrared spectrometer was used in the range of 400–4000 cm⁻¹. -1 The infrared spectrum (ATR-FTIR) of the polyurethane patch was obtained within the specified range. The surface elements of the polyurethane film were determined using Thermo Scientific K-Alpha Nexsa.

[0103] Adhesion performance test:

[0104] The adhesive strength of the polyurethane film was tested using the shear overlap method on a universal testing machine. Pigskin was attached to the top surface of the polyurethane film, with an overlap area of ​​15mm × 25mm. A polyethylene terephthalate film of the same size as the substrate was bonded to the bottom of the polyurethane film with commercial adhesive. A uniaxial tensile force was applied using the universal testing machine, and the force changes were recorded.

[0105] Cell compatibility and antibacterial experiments:

[0106] QLPU75 polyurethane membrane extract was diluted 10, 100, and 1000 times and incubated with L929 cells for 1 and 3 days, respectively. The cytotoxicity of the extract was detected using the MTT assay and a microplate reader. After incubation with L929 cells for 1 and 3 days, the biocompatibility of the QLPU75 polyurethane membrane was assessed by live / dead cell staining. QLPU100, QLPU75, and QLPU0 were cut into squares (10 mm × 10 mm) and adhered to the surface of agar medium. Bacterial suspensions of *Escherichia coli* and *Staphylococcus aureus* were evenly sprayed onto the entire surface of the culture dish, and then incubated at 37°C for 24 hours. The results were observed. The polyurethane patches were then rinsed with sterile PBS, and the bacteria on the patches were ultrasonically peeled off. After culturing, bacterial viability was detected using a microplate reader.

[0107] In vivo hemostasis experiment:

[0108] A rat model of liver hemorrhage was established to evaluate the in vivo hemostatic ability of QLPU75 polyurethane membrane. Before the experiment, female SD rats (weighing 180–220 g) were anesthetized, and the thoracic cavity was opened with surgical scissors to expose the liver. Adjacent body fluids were aspirated, and pre-weighed filter paper was placed under the liver. A 1 cm long and 0.5 cm deep wound was made on the liver with a scalpel. The wound was then treated with gauze or QLPU75 polyurethane membrane, and the weight of the filter paper was measured to evaluate the hemostatic effect.

[0109] In vitro coagulation index (BCI) test:

[0110] QLPU75 polyurethane membranes and gauze were arranged in 24-well plates. Anticoagulated whole blood (20 μL) and CaCl2 (2 μL, 0.25 mol / L) were added, and the plates were incubated at 37°C for 5 minutes. Then, deionized water (2 mL) was added along the plate wall, and the plates were incubated at 37°C for 10 minutes to allow all uncoagulated blood cells to swell and rupture. The supernatant (200 μL) was collected, and the OD value at 540 nm was measured using a microplate reader. Medical gauze served as the control group, and anticoagulated whole blood without calcium chloride solution served as the blank group. BCI was calculated using the following formula:

[0111] BCI (%) = (OD sample) / (OD blank) × 100%

[0112] Study on wound healing ability in rats with infection:

[0113] A full-thickness circular skin wound was created on the back of the rat, and 50 μL of Staphylococcus aureus suspension (1×10⁻⁶) was applied to the wound. 8 (CFU / mL). The wound was treated with QLPU75 polyurethane membrane and commercial dressings, with the untreated group serving as the control group. Wound closure images were taken on postoperative days 0, 1, 3, 7, and 17 to record wound healing progress. Skin tissue was collected from the wound on days 7 and 17, fixed in 4% paraformaldehyde, embedded in paraffin, and stained with hematoxylin-eosin (HE) and Masson's stain.

[0114] Experimental Example 1: Characterization of the bifacial anisotropy of the polyurethane film of the present invention

[0115] like Figure 1 As shown, the water contact angle results indicate that, except for the QLPU100 polyurethane membrane of Example 7, the top of the polyurethane membranes in the other examples exhibits hydrophilicity (34.4°–56.3°), while the bottom exhibits near-hydrophobicity (78.0°–91.1°). The reduction in Q12 content leads to a decrease in the top water contact angle, which may be attributed to increased exposure of hydrophilic components due to the reduction of long alkyl chains on the surface. The QLPU100 polyurethane membrane contains more quaternary ammonium salts, and the hydrophilic components at the top may be effectively shielded by the alkyl chains. Therefore, it exhibits similar hydrophobicity to the bottom.

[0116] like Figure 2 As shown, in the FTIR spectrum, 1705 cm⁻¹ -1 and 1650cm -1 The peaks observed at [location] belong to the carbonyl groups in urethane and urea groups, respectively. The peak at 1705 cm⁻¹ on the top of the QLPUX polyurethane membrane... -1 and 1650cm -1The higher peak intensity at the top indicates a greater presence of urethane and urea groups at the bottom. These urethane and urea groups are more likely to act as active sites, forming hydrogen bonds and other interactions with the substrate surface. This suggests an asymmetric distribution of surface properties between the top and bottom surfaces in the QLPUX polyurethane film, with stronger adhesion occurring more readily at the top than at the bottom.

[0117] XPS was used to analyze the distribution of N elements on both sides of the QLPUX patch. The results are as follows: Figure 3 As shown, the N on the top of the QLPU100 and QLPU75 polyurethane films + The contents were 25.44% and 13.73% respectively, higher than the bottom ones of 18.64% and 11.89%, while no N was detected in the QLPU0 polyurethane film. + The results showed that during the demulsification and film formation process, quaternary ammonium salts migrated to the surface, leading to the formation of N2 on the top of the QLPUX polyurethane film. + The higher ion enrichment results in a higher surface potential. Adding a quaternary ammonium salt to the top of the polyurethane film facilitates electrostatic interaction with the negatively charged substrate.

[0118] Experimental Example 2: Characterization of the adhesion properties of the polyurethane film of the present invention

[0119] like Figure 4 As shown, the top surface of the QLPU75 polyurethane film adheres to various substrates (such as pigskin, glass, stainless steel, and PVC), while the bottom surface has no adhesive ability. The adhesive surface on the top of the patch can easily lift the substrate, but the anti-adhesive surface on the bottom of the patch cannot adhere to or lift the substrate.

[0120] The adhesion strength of the polyurethane film on both sides of the pigskin in the embodiments and comparative examples of the present invention was specifically tested. For example... Figure 5 As shown, all embodiments exhibited adhesiveness at the top, with significantly better adhesion strength at the top than at the bottom. Specifically, the QLPU75 patch achieved an adhesion strength of 23 kPa at the top, 5.63 times that of the bottom. The adhesion of the QLPUX patch decreased with increasing lysine content. The QLPU0 in Comparative Example 2 showed no adhesion at either the top or bottom. Furthermore, as... Figure 6 As shown, compared to QLPU75 volatilized at room temperature for 72 hours in Example 8, the top and bottom adhesion properties of QLPU75-50, QLPU75-75 and QLPU75-100 in Comparative Examples 3, 4 and 5 to pigskin are similar, with no asymmetric surface properties.

[0121] Although the lysine-free QLPU100 polyurethane film exhibits the best adhesion, its poor bulk mechanical properties prevent it from being completely peeled off the substrate surface and provide effective energy dissipation, resulting in adhesion failure occurring within the patch itself rather than at the interface. The QLPU75 polyurethane film offers a better balance between viscoelasticity, adhesion, and mechanical strength. Therefore, the QLPU75 polyurethane film was selected as the optimal choice for subsequent characterization.

[0122] Experimental Example 3: Evaluation of the cell compatibility and antibacterial properties of the polyurethane membrane of the present invention

[0123] The in vitro cytotoxicity of QLPU75 polyurethane membranes was assessed using the MTT assay and live / dead cell staining. Confocal images ( Figure 7 The results showed that L929 cells incubated with QLPU75 polyurethane membranes exhibited normal morphology and showed similar cell viability and proliferation behavior to the control group. MTT assay was used to detect... Figure 8 The results showed that L929 fibroblast viability remained above 80% after 1 and 3 days of culture. These results indicate that QLPU75 polyurethane membranes are non-cytotoxic, biosafe, and have potential application value as a biological adhesive for wound closure.

[0124] To visually evaluate the contact bactericidal effect of QLPU75 polyurethane film, QLPU0 patch was used as a control, and the antibacterial performance of this series of polyurethane patches was characterized by a bacterial solution spraying method. The results are as follows: Figure 9 As shown, bacterial growth was clearly observed on both sides of the QLPU0 polyurethane membrane, while almost no bacterial growth was observed on both sides of the QLPU100 and QLPU75 polyurethane membranes. To further evaluate its antibacterial effect, bacteria on each patch were sonicated and cultured, and quantified by absorbance measurement. The results are as follows. Figure 10 As shown, the QLPU100 polyurethane membrane exhibits slightly higher antibacterial activity compared to the QLPU75 polyurethane membrane. Furthermore, due to the N-type surface of both the QLPU100 and QLPU75 polyurethane membranes... + The content of each substance is higher on the top surface than on the bottom surface, therefore the top surface of both exhibits a better antibacterial effect than the bottom surface.

[0125] Experimental Example 4: Evaluation of the hemostatic performance of the polyurethane membrane of the present invention

[0126] The coagulation ability of polyurethane patches at a specific time point was assessed using a dynamic whole blood coagulation test (BCI). A lower BCI indicated a higher coagulation rate. Figure 11 As shown in Figure a, the BCI values ​​of both gauze and QLPU75 polyurethane membrane were lower than those of the control group, and the BCI value of QLPU75 polyurethane membrane was significantly lower than that of gauze, indicating that it has stronger in vitro coagulation ability. Furthermore, a rat liver hemorrhage model was used to evaluate the hemostatic effect of the polyurethane membrane. Figure 11As shown in b and c, compared with the blank group (~383.3 mg), the amount of bleeding observed in the liver treated with QLPU75 polyurethane membrane (~44.3 mg) was significantly less, indicating that the rapid closure of the wound site and the formation of a physical hemostatic barrier by the QLPU75 polyurethane membrane contributes to effective hemostasis.

[0127] Experimental Example 5: Study on the healing ability of the polyurethane membrane of the present invention on infected wounds

[0128] A circular wound with a diameter of 10 mm was created on the back of anesthetized rats and infected with Staphylococcus aureus. Infected wounds were treated with commercial dressings and QLPU75 polyurethane film, while untreated wounds served as a control group. The wound healing process was photographed and analyzed on days 0, 1, 3, 7, 10, and 17, and the wound closure area was recorded. Over time, the wound area in each group gradually decreased. Figure 12 a). Notably, significant infections were observed in both the control group and the commercial dressing group within the first 3 days, but no infection was observed in the QLPU75 polyurethane membrane group due to its antibacterial properties. After 17 days of treatment, the wound closure rates in the control group, the commercial dressing group, and the QLPU75 polyurethane membrane group were 92.29%, 91.18%, and 97.06%, respectively. Figure 12 b, 12c). Furthermore, HE and Masson staining showed that, compared to other groups, the QLPU75 polyurethane membrane group exhibited stronger healing ability, smaller wound width, and a lower proportion of immature tissue in the wound. Figure 12 d).

[0129] To further investigate wound inflammation, immunofluorescence was used to detect the expression of TNF-α inflammatory factors in wound tissue. Figure 13 As shown, on day 7, due to the antibacterial properties of the quaternary ammonium salt in the QLPU75 polyurethane membrane, the TNF-α (red) expression level in the QLPU75 polyurethane membrane group was significantly lower than that in the control group and the commercial dressing group. Vascular endothelial growth factor (VEGF) plays a crucial role in promoting physiological activities such as angiogenesis and collagen regeneration related to wound healing. Figure 13 The results showed that VEGF (green) was expressed in all wounds after 17 days, with the QLPU75 polyurethane membrane group exhibiting the highest VEGF expression level. These results indicate that the polyurethane membrane of this invention has good anti-infection and wound healing promoting effects.

[0130] In summary, the polyurethane film prepared by this invention using specific raw materials and methods exhibits a unique asymmetry, with one side being adhesive and the other side being anti-adhesive. As an asymmetric adhesive Janus bioadhesive patch, the adhesive side can effectively achieve biological tissue adhesion and wound closure, while the anti-adhesive side can effectively prevent adhesion of normal tissue. At the same time, the introduction of quaternary ammonium salt gives the patch good antibacterial properties, which can promote skin wound closure and infected wound healing.

Claims

1. A waterborne polyurethane, characterized in that, It is prepared from the following raw materials in the following molar proportions: 5-15 parts of soft segment component, 11-42 parts of diisocyanate, and 5-15 parts of chain extender; wherein the soft segment component is a mixture of hydrophilic and hydrophobic soft segments, and the hydrophobic soft segment accounts for 20%-100% of the molar fraction of the soft segment component; wherein the hydrophilic soft segment is a hydrophilic diol or a hydrophilic diamine, and the hydrophobic soft segment is a hydrophobic diol or a hydrophobic diamine; wherein the chain extender is a quaternary ammonium salt chain extender or a mixture thereof with a non-quaternary ammonium salt chain extender; The structure of the quaternary ammonium salt chain extender is shown in Formula I: 。 2. The waterborne polyurethane as described in claim 1, characterized in that, It is prepared from the following raw materials in the following molar proportions: 8-12 parts of soft segment component, 20-25 parts of diisocyanate, and 8-12 parts of chain extender; the hydrophobic soft segment accounts for 50%-83% of the molar fraction of the soft segment component; the molar fraction of the non-quaternary ammonium salt chain extender in the chain extender is 0%-75%.

3. The waterborne polyurethane as described in claim 2, characterized in that, It is prepared from the following raw materials in the following molar proportions: 10 parts of soft segment component, 22 parts of diisocyanate, and 10 parts of chain extender; the hydrophobic soft segment accounts for 83% of the molar fraction of the soft segment component; and the non-quaternary ammonium salt chain extender accounts for 25% of the molar fraction of the chain extender.

4. The waterborne polyurethane as described in claim 1, characterized in that, The hydrophilic soft segment is selected from one or more of PEG and Ymer N-120; The hydrophobic soft segment is selected from one or more of hydrophobic polyether diols, polyester diols, polysiloxane diols, and polycarbonate diols; The diisocyanate is selected from any one or more of lysine-derived diisocyanate, hexamethylene diisocyanate, trimethyl 1,6-hexamethylene diisocyanate, isophorone diisocyanate, cyclohexanedimethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, or 1,4-cyclohexane diisocyanate. The non-quaternary ammonium salt chain extender is any one or more of ethylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, 1,4-cyclohexanediol, dimethylolpropionic acid, diethylene glycol, tetraethylene glycol, hydrazine, ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,6-hexanediamine, isophoronediamine, ethanolamine, propanolamine, or lysine.

5. The waterborne polyurethane as described in claim 4, characterized in that, The hydrophilic soft segment is PEG; the hydrophobic soft segment is PPG or PTMG; the diisocyanate is isophorone diisocyanate; and the non-quaternary ammonium salt chain extender is lysine.

6. A waterborne polyurethane emulsion, characterized in that, The product is obtained by emulsifying and dispersing the aqueous polyurethane as described in any one of claims 1 to 5 in water.

7. The method for preparing the aqueous polyurethane emulsion according to claim 6, comprising the following steps: (1) The dry and anhydrous soft segment component is added with diisocyanate and catalyst under inert gas protection and reacted at 78~82℃ for 1.5~2.5h; (2) Cool to room temperature, add quaternary ammonium salt chain extender, and react at 53~56℃ for 2.5~3.5h; (3) No non-quaternary ammonium salt chain extender is added, or a non-quaternary ammonium salt chain extender is added and the reaction is carried out at room temperature for 3-8 minutes; (4) Emulsify by stirring at a speed of more than 1000 rpm for 0.8~1.2h.

8. The preparation method according to claim 7, characterized in that, The catalyst in step (1) is organic bismuth, the amount of which is 1‰ of the total amount of raw materials, the reaction temperature is 80℃, and the time is 2h; The reaction temperature in step (2) is 55℃, and the reaction time is 3h; The reaction time at room temperature for adding the non-quaternary ammonium salt chain extender in step (3) is 5 minutes. The stirring and emulsification time in step (4) is 1 hour.

9. A polyurethane membrane, characterized in that, It is prepared by drying the aqueous polyurethane emulsion according to claim 6 to remove the solvent; The preparation method includes the steps of pouring the aqueous polyurethane emulsion of claim 6 into a mold and drying it at room temperature for more than 48 hours.

10. The polyurethane membrane as described in claim 9, characterized in that, The preparation method is as follows: Pour the aqueous polyurethane emulsion according to claim 6 into a mold, dry at room temperature for 70-75 hours, dry at 45-55°C for 45-50 hours, and then vacuum dry at 45-55°C for 45-50 hours.

11. A method for preparing a polyurethane membrane, characterized in that, This includes the step of pouring the waterborne polyurethane emulsion into a mold and drying it at room temperature for more than 48 hours. The aqueous polyurethane emulsion is obtained by emulsifying and dispersing aqueous polyurethane in water; the raw materials for preparing the aqueous polyurethane include a quaternary ammonium salt chain extender; the structure of the quaternary ammonium salt chain extender is shown in Formula I: 。 12. The preparation method according to claim 11, characterized in that, Includes the following steps: (a) Pour the aqueous polyurethane emulsion of claim 6 into a mold and dry at room temperature for 70-75 hours; (b) Dry at 45~55℃ for 45~50h; (c) Vacuum drying at 45~55℃ for 45~50h.

13. Use of the aqueous polyurethane according to any one of claims 1 to 5, or the aqueous polyurethane emulsion according to claim 6, or the polyurethane film according to any one of claims 9 to 10, in the preparation of adhesive patches.

Citation Information

Patent Citations

  • Biquaternary ammonium salt-containing diamine or diol monomer, preparation method of monomer, water-based non-toxic antibacterial polyurethane emulsion prepared by monomer, and preparation method of emulsion

    CN103420868A

  • Aqueous polyurethane material with hydrophilic outer layer and hydrophobic inner layer, preparation method and applications

    CN108840991A